Beam-Element Model of Bridge Truss Girders Regarding Joint Dimensions - Łodygowski, T.; Siekierski, W. (Engineering Transactions, 2015)
The paper concerns modelling of bridge truss girders with regard to joint (gusset plates) dimensions. Modification of the classical beam-element numerical model is presented. It is based on introduction of additional near-node beam elements of lengths corresponding to joint dimensions. Their stiffnesses are determined in the iterative procedure. Results of finite element method analyses of the "accurate" (shell element) and dynamically modified "simplified" (beam element) models of Structural joint with a part of connected members are compared. Laboratory tests that verify the iterative procedure are described. The calculated and recorded displacements and internal forces are compared.